Mucosal-Associated Invariant T Cells Expressing the TRAV1-TRAJ33 Chain Are Present in Pigs - Xiao, Xingxing; Li, Kun; Ma, Xueting; Liu, Baohong; He, Xueyang; Yang, Shunli; Wang, Wenqing; Jiang, Baoyu; Cai, Jianping (Frontiers in Immunology, 2019)
Mucosal-associated invariant T (MAIT) cells are a subpopulation of evolutionarily conserved innate-like T lymphocytes bearing invariant or semi-invariant TCRα chains paired with a biased usage of TCRβ chains and restricted by highly conserved monomorphic MHC class Ⅰ-like molecule, MR1. Consistent with their phylogenetically conserved characteristics, MAIT cells have been implicated in host immune responses to microbial infections and non-infectious diseases, such as tuberculosis, typhoid fever and multiple sclerosis. To date, MAIT cells have been identified in humans, mice, cows, sheep, and several nonhuman primates, but not in pigs. Here, we cloned porcine MAIT (pMAIT) TCRα sequences from PBMC cDNA, and then analyzed the TCRβ usage of pMAIT cells expressing the TRAV1-TRAJ33 chain, finding that pMAIT cells use a limited array of TCRβ chains (predominantly TRBV20S and TRBV29S). We estimated the frequency of TRAV1-TRAJ33 transcripts in peripheral blood and tissues, demonstrating that TRAV1-TRAJ33 transcripts are expressed in all tested tissues. Analysis of the expression of TRAV1-TRAJ33 transcripts in three T-cell subpopulations from peripheral blood and tissues showed that TRAV1-TRAJ33 transcripts can be expressed by CD4+CD8-, CD8+CD4-, and CD4-CD8- T cells. Using a single-cell PCR assay, we demonstrated that pMAIT cells with the TRAV1-TRAJ33 chain express cell surface markers IL-18Rα, IL-7Rα, CCR9, CCR5, and/or CXCR6, and transcription factors PLZF, and T-bet and/or RORγt. In conclusion, pMAIT cells expressing the TRAV1-TRAJ33 chain have characteristics similar to human and mouse MAIT cells, further supporting the idea that the pig is an animal model for investigating MAIT cell functions in human disease.